Large-scale wind power integration in Nordland - Solvang, Tarjei Benum (Institutt for elkraftteknikk, 2007)
Nord-Norsk Vindkraft AS is planning to build two wind farms in Nordland, Norway. The wind farms are located at Sleneset and Sjonfjellet. The planned total installed power is 653 MW. An important part of the planning phase is to perform steady-state and dynamic analyses, to simulate the impacts from the wind farms on the existing power system in the area. The steady-state analysis is performed by Norsk Systemplan og Enøk AS (NORSEC). The project presented in this master thesis is part of the dynamic analysis. The overall objective for this project is to illustrate the dynamic impacts from the wind farms on the existing power system and the differences in impact depending on the various control strategies being used. The following elements are included in the assignment: - Establish a steady-state and dynamic grid model describing the power system in question. - Determine whether the wind farms are able to reach full production during different configurations without reaching an unacceptable operating state. - Examine the impact from and behaviour of transformers with load tap changers. - Illustrate the differences between different control modes in the wind farm connection point. The model used in this project is established by converting the steady-state model used in the steady-state analysis from Netbas to SIMPOW. The time in the steady-state model is set to January 2009. The steady-state model is then expanded by introducing aggregated doubly-fed induction generators for power production in the wind farms. For some of the simulations, a static VAR compensator is inserted at Bardal. The dynamic model is established by introducing a dynamic description of the components in the steady-state model. Due to lack of dynamic data, typical values are used for some of the components. The comparison between the power flows from the basic model provided by NORSEC and the initial converted SIMPOW model show small differences in reactive power flow. These differences were, however to be expected, due to changes made when ...